Hydrophilic spongy biochar crosslinked with starch and polyvinyl alcohol biocarrier for nitrate, phosphorus, and cadmium removal in low carbon wastewater: Enhanced performance mechanism and detoxification. (October 2022) - Zhang, Shuai; Su, Junfeng; Ali, Amjad; Huang, Tinglin; Sun, Yi; Ren, Yi
Graphical abstract: Highlights: Bioreactor with spongy biocarrier achieves efficient removal of Cd2+, NO3 – and TP. Biofilm shedding, Cd2 + efflux and biogenic precipitation favor Cd2 + and P removal. WSB promotes pore size and reduces effluent fluorescent SMPs. Energy-related mechanisms and key genes for denitrification are enhanced. Abstract: This study aims to develop a functional biocarrier with hydrophilic spongy biochar crosslinked with starch and polyvinyl alcohol (WSB/starch-PVA) for simultaneous removal of NO3 – -N, total phosphorus (TP) and Cd 2+ in low carbon wastewater. Results showed that the WSB/starch-PVA bioreactor achieved the maximum NO3 – -N removal efficiency in subphase 1.2 with 98.07 % (3.64 mg L −1 h −1 ) versus control (75.30 %, 2.81 mg L −1 h −1 ), and removed 54.84 % and 73.97 % of TP and Cd 2+ . Material characterization suggested that functional groups (related to C, N and O) on biocarrier and biofilm, and biogenic co-precipitation facilitated TP and Cd 2+ removal. The WSB made the biocarrier pores larger and regular, and decreased fluorescent soluble microbial products. The predicted metagenome further suggested that central citrate cycle, oxidative phosphorylation of bio-community, and NO3 – -N removal were enhanced. Functions for microbial induced co-precipitation, Cd 2+ transport/efflux, antioxidants, and enhanced biofilm formation favored the NO3 – -N/TP removal and Cd 2+ detoxification.